The viability of the all-electric aircraft in commercial aviation - Klein, Logan (Kansas State University, 2023)
This report addresses the viability of all-electric aircraft systems in the commercial aviation industry. The industry is driving the need for these types of systems to accomplish the goals of reducing emissions and noise, while increasing overall system efficiency. This effort, however, brings along many unique challenges that are novel to engineers and require a different design perspective than conventional combustion engine aircraft. The works of multiple researchers are brought together in this study to analyze all the challenges engineers currently face with system weight, performance, and integration into the commercial aviation market. The results of multiple computer models ranging from short-range commuter aircraft to larger airline designs are compared and referenced in the discussion of electric aircraft viability. The safety and redundancy of all-electric designs are also analyzed to determine the risk factor behind aircraft relying solely on electrical power. The purpose of this report is to analyze and critique the concept of all-electric propulsion systems for commercial operations to determine whether these aircraft have the potential to meet industry goals of reducing emissions and noise while also increasing the safety and efficiency of the whole system.
Keywords: Electrification; Electric aircraft; Electric propulsion systems; Commercial aircraft; Emissions